MENGUNGKAP PERAN KARAKTERISTIK INTERNAL PERUSAHAAN DALAM PENGGUNAAN NEGARA SURGA PAJAK: EXPLORING THE ROLE OF INTERNAL FIRM CHARACTERISTICS IN TAX HAVEN UTILIZATION - Aprilia, Sabrina Dwi; Amelia, Yessica; Permana, Ngadi (Universitas Riau, 2025)
The use of tax havens remains a critical issue in international taxation, posing challenges to the effectiveness of national revenue collection. This study aims to investigate the effects of intangible assets, multinationality, thin capitalization, transfer pricing, capital intensity, and firm size on the likelihood of utilizing tax havens. Based on 126 firm-year observations from companies listed on the Indonesia Stock Exchange (IDX) between 2021 and 2023, the study employs a quantitative approach using multiple linear regression analysis, supported by classical assumption testing, t-tests, F-tests, and R² analysis. The empirical results reveal that multinationality, capital intensity, and firm size have a significant positive influence on tax haven utilization, while thin capitalization shows a significant negative effect. In contrast, intangible assets and transfer pricing are found to have no significant effect. Collectively, all independent variables significantly affect tax haven utilization. These findings suggest that tax haven usage is driven by a complex interplay of internal firm characteristics rather than any single factor. This study contributes to the literature on international tax planning and provides practical implications for regulators to strengthen risk-based fiscal supervision and mitigate aggressive tax strategies.